Understanding and representing atmospheric convection across scales: recommendations from the meeting held at Dartington Hall, Devon, UK, 28–30 January 2013. (13th May 2014) - Holloway, Christopher E.; Petch, Jon C.; Beare, Robert J.; Bechtold, Peter; Craig, George C.; Derbyshire, Stephen H.; Donner, Leo J.; Field, Paul R.; Gray, Suzanne L.; Marsham, John H.; Parker, Douglas J.; Plant, Robert S.; et al.
Abstract As weather and climate models move towards higher resolution, there is growing excitement about potential future improvements in the understanding and prediction of atmospheric convection and its interaction with larger‐scale phenomena. A meeting in January 2013 in Dartington, Devon was convened to address the best way to maximise these improvements, specifically in a UK context but with international relevance. Specific recommendations included increased convective‐scale observations, high‐resolution virtual laboratories, and a system of parameterization test beds with a range of complexities. The main recommendation was to facilitate the development of physically based convective parameterizations that are scale‐aware, non‐local, non‐equilibrium, and stochastic.